Improving T-Kick Accuracy in Pencak Silat Through Rope Limiter Focused Training: A Trauma-Free Approach for Beginner Students - Hana Mindayanti; Dinar Dinangsit; Muhammad Nur Alif (Universitas Tadulako, 2026)
This study aims to test a focused training method, namely with a rope barrier to improve the accuracy of T kicks and student safety in beginner pencak silat training. This study was driven by two common problems in beginner training, first is poor kick accuracy and second is that rigid training equipment can also cause injuries. The data of this study used a quantitative research approach with a quasi-experimental non-equivalent control group design. A total of 111 students from 18 dynamic physics classes participated in this study, with 57 of them as the experimental group and the remaining 54 students as the control group. The experimental group trained with ropes, while the control group trained with chair-based media. Data were analyzed using the Wilcoxon Signed Rank Test and the Mann–Whitney U Test. Results In both groups, the pre-test showed a significant increase after participating in this training session (experimental group: p < 0.001; control group: p < 0.001). However, the difference between groups was not significant (p = 0.994) which means that both training methods improved the accuracy of T kicks in steady state to a similar value. Regardless, rope barriers serve as a safer and more versatile training environment by minimizing impact compared to rigid chairs. Conclusion Rope barriers are a simple, inexpensive, and safe alternative for basic pencak silat training at the elementary level.